Innovations in Undergraduate Research Training Through Multisite Collaborative Programming: American Heart Association Summer Undergraduate Research Experience Syndicate - Tinuola B. Ajayi; Adrienne L. Mueller; Ike S. Okwuosa; Asha Barshilia; Joseph C. Wu; Emelia J. Benjamin; Joey V. Barnett; Kendra H. Oliver (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background To support diversity in biomedical science, the American Heart Association launched the Supporting Undergraduate Research Experiences for undergraduate students from underrepresented backgrounds to provide mentorship and high‐level exposure at 5 leading medical institutions. Here we describe the initial formation of the partnership and the alteration made in response to the program to accommodate COVID‐19 safety precautions. Methods and Results We outline how programming shifted from local, in‐person programming in the summer of 2019 to a collaborative, mainly virtual curriculum in 2020 using students’ self‐reported before and after surveys from both 2019 (n=33) and 2020 (n=42). Students from both in‐person (2019) and virtual programs (2020) self‐reported significant gains in scientific proficiency. A qualitative‐directed content analysis of student open‐response questions was performed. Students reported extensive benefits from the 2020 virtual training, including Personal Gains, Research Skills, Thinking and Working Like a Scientist, and Attitudes and Behaviors. Notedly, we observed increases in the Attitudes and Behaviors category. We outline the pros and cons of in‐person and virtual programming and make recommendations moving forward in a postpandemic world with hybrid work and learning systems. Conclusions Our effort informs the development of future undergraduate research training programs, significantly maximizing a hybrid training modality. The American Heart Association Supporting Undergraduate Research Experiences serves as a model for building multi‐institutional partnerships and providing research experiences that overcome institutional barriers and support students' interests, commitment, and ability to persist in science, technology, engineering, and math fields.